Tempests and slaughter : a Tortall legend - Pierce, Tamora (Numair chronicles, 2018)
Arram Draper, Varice Kingsford, and Ozorne Tasikhe forge a bond of friendship that sees them through many changes as student mages at Imperial University of Carthak.